Elements and factors involved in tissue-specific and embryonic expression of the liver transcription factor LFB1 in Xenopus laevis. - Zapp, D (1993)
LFB1 (HNF1) is a tissue-specific transcription factor found in the livers, stomachs, intestines, and kidneys of vertebrates. By analyzing the promoter of the Xenopus LFB1 gene, we identified potential autoregulation by LFB1 and regulation by HNF4, a transcription factor with a tissue distribution similar to that of LFB1. Injection of LFB1 promoter-chloramphenicol acetyltransferase constructs into Xenopus eggs revealed embryonic activation that is restricted to the region of the developing larvae expressing endogeneous LFB1. Proper embryonic activation was also observed with a rat LFB1 promoter. Deletion analysis of the Xenopus and rat promoters revealed that in both promoters embryonic activation is absolutely dependnet on the presence of an element that contains CCNCTCTC as the core consensus sequence. Since this element is recognized by the maternal factor OZ-1 previously described by N. Ovsenek, A. M. Zorn, and P. A. Krieg (Development 115:649-655, 1992), we might have identified the main constituents of a hierarchy that leads via LFB1 to the activation of tissue-specific genes during embryogenesis.